2014
DOI: 10.1109/jsen.2014.2326337
|View full text |Cite
|
Sign up to set email alerts
|

The Microloop-Gap Resonator: A Novel Miniaturized Microwave Cavity for Double-Resonance Rubidium Atomic Clocks

Abstract: Abstract-Nowadays mobile and battery-powered applications push the need for radically miniaturized and low-power frequency standards that surpass the stability achievable with quartz oscillators. For the miniaturization of double-resonance rubidium ( 87 Rb) atomic clocks, the size reduction of the microwave cavity or resonator (MWR) to well below the wavelength of the atomic transition (6.835 GHz for 87 Rb) is of high interest. Here, we present a novel miniaturized MWR, the μ-LGR, for use in a miniature DR ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…More recently, CPT has been used in vapor cell clocks, 36,37 including CPT masers. [38][39][40][41] Most chip-scale atomic clocks rely on coherent population trapping, although new miniature microwave cavities 42 remain a viable alternative for miniaturized atomic clocks. A review of the application of CPT to atomic clocks can be found in Ref.…”
Section: Vapor Cell Atomic Clocksmentioning
confidence: 99%
“…More recently, CPT has been used in vapor cell clocks, 36,37 including CPT masers. [38][39][40][41] Most chip-scale atomic clocks rely on coherent population trapping, although new miniature microwave cavities 42 remain a viable alternative for miniaturized atomic clocks. A review of the application of CPT to atomic clocks can be found in Ref.…”
Section: Vapor Cell Atomic Clocksmentioning
confidence: 99%
“…G.-X. Du, T. Bandi, A. Horsley, P. Treutlein, and G. Mileti,3 The design and study of different types of microwave resonator cavities with well-defined field distributions have been addressed, e.g., for compact vapor cell atomic clocks [11] and H-masers [12], high-performance Rb clocks based on the continuous-wave (cw) [13], [14] or pulsed optical pumping (POP) approach [6,15], or miniaturized Rb clocks [16], [17]. In primary atomic fountain clocks, effects such as distributed phase shifts in the cavity can become relevant [18].…”
Section: Introductionmentioning
confidence: 99%
“…MEMS alkali vapor cell technology, utilizing eutectic bonding, has been investigated for years [65,66,67,68,69,70]. According to this technology, the silicon–glass preform and glass cover, kept at a distance, are located in the vacuum chamber.…”
Section: Methods Of Mems Vapor Cell Fabricationmentioning
confidence: 99%